Use and reuse of visual resources in student papers and presentations. Issue 3 (3rd June 2019) - Matusiak, Krystyna K.; Harper, Anna; Heinbach, Chelsea
Abstract : Purpose: The purpose of this study is to explore how undergraduate and graduate students use visual resources in their papers and presentations and what role images play in their academic work. It also focused on analyzing the types of image use/reuse in academic work. Design/methodology/approach: This study was designed using an exploratory, qualitative approach. In all, 15 participants were recruited. Multiple sources of data were collected, including visual evidence, questionnaires and interviews. It adopted consensual qualitative research for data analysis. Findings: This study finds a prevalent reuse of images in student presentations but limited use and reuse in papers. Images in presentations were primarily reused as objects for engaging and esthetic purposes. Reuse of images as a source of information was not common and in some cases problematic when students were missing context. The type of use/reuse of images in the papers was more varied with examples of creative use and transformative reuse. Practical implications: This paper contributes to a better understanding of how students use and reuse images for academic papers and presentations. Results have important implications for teaching visual literacy and re-purposing images in higher education. Originality/value: This paper analyses educational use/reuse of images along the data/object spectrum and distinguishes between different types of image use and reuse.